METHODICAL TECHNIQUES FOR CALCULATION OF TARIFFS IN ROAD FREIGHT TRANSPORT (Perner's Contacts, 2012)
The article discusses the methodology for the design of tariffs for road freight transport. Tariff can be compiled based on the available data and relevant methodology and offered to customer.
Keywords: tariff, carrier , coasts, semi-trailer